PENGARUH KEPRIBADIAN PROAKTIF TERHADAP INTENSI KEWIRAUSAHAAN MAHASISWA : PENDIDIKAN KEWIRAUSAHAAN SEBAGAI VARIABEL MODERASI - Aryaningtyas, Aurilia Triani; Palupiningtyas, Dyah (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 13 Nomor 1 Tahun 2019DO - 10.24843/MATRIK:JMBK.2019.v13.i01.p02, 2019)
This study investigated the predictive relationship between proactive personality and entrepreneurial intention and the extent to which such a relationship was moderated by entrepreneurial education. Using sample 200 undergraduates students at ten universities in Semarang by quota sampling technique. The results showed that proactive personality was significantly and positively associated with entrepreneurial intention. Entrepreneurial education related significantly with entrepreneurial intention. It was observed that entrepreneurial education significantly moderated the relationship between proactive personality and entrepreneurial intention. The findings were consistent with the personality theory of entrepreneurship. The implications of this research can be used for those who strive in higher education, how they supposed to design the right pattern of entrepreneurship education to encourage more students improve their e ntrepreneurial intention.